Остров последнего злодея: роман / Э. Веркин - Веркин Эдуард Николаевич (Космические приключения, 2009)
Экземпляры: СФ-2 (20101917) / Инвентарный номер: 39088z2 / Цена: 132.00 / Сис.шифр: 84(2) / Авт.знак: В 32 / ГРНТИ: 17.82.31 / ББК: 84(2=Рус)